PENGESAHAN ANAK LUAR KAWIN YANG DIAKUI AYAH BIOLOGIS MELALUI PENGADILAN - Rizal, Said (jurnal.unprimdn.ac.id, 2023)
Following the issuance of Constitutional Court Decision Number 46/PUU-VIII/2010 concerning amendments and additions to Article 43 of Law Number 1 of 1974 concerning Marriage, significant changes have been made to family law in Indonesia. These changes pertain specifically to the status of children born out of wedlock who may now be legitimized. Constitutional Court Decision Number 46/PUU-VIII/2010 declares and confirms that children born out of wedlock can now have civil relationships with their biological fathers akin to legitimate children, not only with their mothers and maternal families. Previously, children born out of wedlock only had civil relationships with their mothers and maternal families. To establish a civil relationship with a child born out of wedlock, the biological father must acknowledge paternity. In practice, the biological father can acknowledge paternity by petitioning the District Court, and the custody rights over the child born out of wedlock lie with the biological father. This can be substantiated through scientific and technological evidence or other legal evidence. The research conducted is of a normative legal nature, and the data analysis employs a qualitative descriptive method